Ways to increase adherence to allergen immunotherapy. (3rd June 2019) - Pitsios, Constantinos; Dietis, Nikolas
Abstract: Adherence to allergen immunotherapy (AIT) is crucial for its efficacy. Subcutaneous AIT requires monthly visits (or more extended in the case of venom immunotherapy), while sublingual AIT is performed with a daily intake of allergen drops. Non-adherence to an AIT schedule and premature discontinuation are common problems. Various studies have shown controversial results on the rate of AIT adherence. The aim of this review is to describe the problem of non-adherence and to offer some evidence-based advice to allergologists on how to increase it. Better patient education at the beginning of treatment, sharing with patients the decision on which type of immunotherapy to select and showing sincere interest in their treatment concerns are some tips that can help to increase adherence. A well organized allergologist time schedule not only increases safety but also offers the possibility of close follow-up and an increase in patient loyalty.